A Comparative Analysis of Biology Learning Outcomes of Grade 10 Students Using Independent Questions - Alya Febrina Azzahra; Hanafi Reviana; Yastin Indriawati; Muncar Sundari; Suwarto (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
This study aims to compare the biology learning outcomes of students in classes X E4 and X E5 at SMA Veteran 1 Sukoharjo. Sukoharjo (a senior high school). The study used a descriptive quantitative method with an instrument in the form of a multiple-choice biology test consisting of 10 questions. The research sample involved all students in classes X E4 and X E5 in the 2025/2026 academic year, with a total of 76 respondents. Descriptive statistical analysis was conducted to obtain an initial overview of the students' Biology test results, while the prerequisite analysis tests included normality and homogeneity of variance tests. The normality test results showed that the student learning outcome data in both classes were normally distributed, and the homogeneity test results showed that the data variance was homogeneous, thus fulfilling the requirements for an independent two-sample t-test. The t-test results showed a significance value of Sig. (2-tailed) of 0.530 (> 0.05), indicating that there was no significant difference between the biology learning outcomes of students in classes X E4 and X E5 at SMA Veteran 1 Sukoharjo